PENGARUH DANA PERIMBANGAN, PENDAPATAN ASLI DAERAH, UKURAN PEMERINTAH DAERAH, BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Regita Oktaviani, (2020)
This research aims to examine and verify the effect of balance fund, locally-generated revenue, local goverment size, and capital expenditure on financial performance of local geverment. This research uses districts/cities in Sulawesi Island in 2016-2018. sampling technique uses sensus sampling method is 243 samples in Sulawesi Island. Hypothesis test in this research is multiple linear regression with SPSS. The result of this research is (1) balance fund have negative effect (2) locally-generated revenue have significant effect (3) local goverment size have no significant effect (4)and capital expenditure have significant effect on financial performance of local goverment. The contribution in this research is give recommendation to increase financial performance of local goverment and to the next researcher add variables not examined in this research